TALISMANIC PRACTICE AT LEFKANDI: TRINKETS, BURIALS AND BELIEF IN THE EARLY IRON AGE. (December 2016) - Arrington, Nathan T.
Abstract : Excavations at Lefkandi have dispelled much of the gloom enshrouding the Early Iron Age, revealing a community with significant disposable wealth and with connections throughout the Mediterranean. The eastern imports in particular have drawn scholarly attention, with discussion moving from questions of production and transportation to issues surrounding consumption. This article draws attention to some limitations in prevalent socio-political explanations of consumption at Lefkandi, arguing that models relying on gift-exchange, prestige-goods and elite display cannot adequately account for the distribution, chronology, find context and function of imports at Lefkandi. A study of trinkets – small but manifestly foreign imports of cheap material – offers a new perspective. An analysis of their form, context, use and meaning demonstrates that trinkets were meaningfully and deliberately deposited with children as talismans or amulets. Talismanic practice had Late Bronze Age precedents, and in the Early Iron Age was stimulated from personal contact with the Near East or Cyprus and nurtured by the unique mortuary landscape at Lefkandi. This article demonstrates the need for archaeologists to treat mortuary beliefs as a meaningful explanatory variable. Moreover, the ability of non-elite objects to convey powerful ideas has important implications for the nature and dynamics of artistic and cultural exchanges between Greece and the East in the Iron Age.